DATA MODELLING SOLUTION FOR REFLECTIVE ePORTFOLIO SYSTEM - Gorbunovs, Aleksandrs; Gorbunovs, Dainis; Kapenieks, Atis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
An importance of creating of efficacious information systems, which would enhance learning outcomes, leads to development of appropriate models.Modelling process with further validation and verification of developed information system or technological solution is essential. This paper displays the considerations and efforts made to work out such model in a form of reflection stimulating and learning outcomes enhancing ePortfolio information system. The authors introduce architecture of developed system from a view of used technologies, system’s algorithmic model and data model, as well its approbation results in Living Lab.